Caracterización anatómica ultraestructural de las variantes “Atlántica”, “Sur” y “Cebolla” del bambú, Guadua angustifolia (Poaceae: Bambusoideae), en Costa Rica - Montiel, Mayra; Jiménez, Víctor M.; Guevara, Eric (Revista de Biología Tropical, 2006)
We present an ultrastructural characterization of three variants or “forms” of Guadua angustifolia and of the closely related Guadua sp., from Costa Rican populations. Their ultrastructure is similar. Differences are: the absence of trichomes in the abaxial epidermis of leaf lamina in “Cebolla” and hook-shaped trichomes in the lamina of Guadua “Sur” or “Mansa”. Trichomes were bicellular in “Atlántica” or “Brava”. In the adaxial section of the culm sheaths, “Cebolla” lacks trichomes, “Sur” has abundant and long unicellular trichomes, and “Atlántica” has scarce trichomes (trichomes are an important taxonomic characteristic for differentiation of bamboo variants, and they facilitate genotype identification). The bulliform cells present the following variation: large and segmented in G. “Cebolla”; of medium size in G. “Sur”, and thin and grouped in G. “Atlántica”. Rev. Biol. Trop. 54(Suppl. 2): 1-12. Epub 2006 Dec. 01.